2021
DOI: 10.1038/s41598-021-92994-3
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genomes of two Polydora (Spionidae) species provide further evidence that mitochondrial architecture in the Sedentaria (Annelida) is not conserved

Abstract: Contrary to the early evidence, which indicated that the mitochondrial architecture in one of the two major annelida clades, Sedentaria, is relatively conserved, a handful of relatively recent studies found evidence that some species exhibit elevated rates of mitochondrial architecture evolution. We sequenced complete mitogenomes belonging to two congeneric shell-boring Spionidae species that cause considerable economic losses in the commercial marine mollusk aquaculture: Polydora brevipalpa and Polydora webst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
3
4
0
Order By: Relevance
“…Isolation and sequencing of total genomic DNA from this specimen enabled assembly of the mitochondrial genome. In this genome, we found all standard metazoan protein-coding genes (PCGs), rRNAs, tRNAs, duplicated tRNAs, as well as four additional regions that were also previously found in P websteri, P brevipalpa , and P. hoplura species (Ye et al 2021;Lee& Lee 2022). Similar to other polychaetes, all genes were encoded on a single strand (Figure 1).…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Isolation and sequencing of total genomic DNA from this specimen enabled assembly of the mitochondrial genome. In this genome, we found all standard metazoan protein-coding genes (PCGs), rRNAs, tRNAs, duplicated tRNAs, as well as four additional regions that were also previously found in P websteri, P brevipalpa , and P. hoplura species (Ye et al 2021;Lee& Lee 2022). Similar to other polychaetes, all genes were encoded on a single strand (Figure 1).…”
Section: Resultssupporting
confidence: 71%
“…Recently, three complete mitogenomes of shell-boring Polydora species, P. websteri, P. brevipalpa , and P. hoplura , were sequenced (Ye et al 2021; Lee & Lee 2022). Analysis of two related species, P. websteri and P. brevipalpa , and comparisons to other sedentary animals showed that Polydora mitogenomes have some unusual features: the gene order has been changed, and there are four non-coding regions that are longer than 500 bp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleotide composition of the mitogenome was 37.66% T, 15.04% C, 35.21% A, and 12.09% G, with a strong A + T bias of 72.87%, which is similar to other annelids (Ye et al. 2021 ). The G + C content of protein-coding genes was 26.61% (length: 11,134 bp), tRNAs 26.79% (length: 1,407 bp), and rRNAs 53.54% (length: 1,903) ( Supplementary Data ).…”
supporting
confidence: 53%
“…The architecture of the annelid mitochondrial genome is generally well conserved ( Weigert et al 2016 ), with some notable exceptions, for example, Ramisyllis multicaudata from the family Syllide ( Aguado et al 2015 ). Moreover, recently three complete mitogenomes of shell-boring Polydora species (Spionidae family), Polydora websteri , Polydora brevipalpa , and Polydora hoplura , were sequenced ( Ye et al 2021 ; Lee and Lee 2022 ). Analysis of two related species, P. websteri and P. brevipalpa , and comparisons with other sedentary animals showed that Polydora mitogenomes have some unusual features: the gene order has been changed, and there are four NCRs that are longer than 500 base pairs (bp).…”
Section: Introductionmentioning
confidence: 99%